Partner support and anxiety in young women with breast cancer. Issue 12 (13th March 2015) - Borstelmann, Nancy A.; Rosenberg, Shoshana M.; Ruddy, Kathryn J.; Tamimi, Rulla M.; Gelber, Shari; Schapira, Lidia; Come, Steven; Borges, Virginia; Morgan, Evan; Partridge, Ann H.
Abstract: Objective: Using a large prospective cohort of women age 40 or younger diagnosed with breast cancer, we examined the relationship between perceived partner support and anxiety. Methods: Six hundred seventy‐five young women with breast cancer Stages I–III, median age 36, completed a self‐report baseline questionnaire. Perceived partner support was assessed using items extracted from the marital subscale of the Cancer Rehabilitation Evaluation System; generalized social support was assessed with the Medical Outcomes Study–Social Support Survey. Anxiety was measured using the anxiety subscale of the Hospital Anxiety and Depression Scale. Multivariable logistic regression analyses evaluated the association between partner support, other sociodemographic factors, and anxiety. Results: Mean age at diagnosis was 35.4 years. Fourteen percent of the women were not partnered, and among those who were partnered or in a significant relationship, 20% were categorized as unsupported. In univariate and multivariable analysis adjusting for sociodemographic factors, women in an unsupported‐partnered relationship had higher odds of anxiety symptoms compared with women in a supported‐partnered relationship. Young age and being financially insecure were also both independently associated with anxiety. Conclusions: Our findings suggest that partner support may play a key role in a young woman's adjustment to a serious stressor such as breast cancer. In addition, younger age increases vulnerability to anxiety as does struggling with finances. Because supportive efforts of a partner have potential to protect against the impact of stress, interventions to enhance partner support and reduce anxiety might be beneficial to address challenges experienced as a couple in this setting. Copyright © 2015 John Wiley & Sons, Ltd.